Simultaneous determination of plasma nicotine and cotinine by UHPLC–MS/MS in C57BL/6 mice and its application in a pharmacokinetic study. (9th August 2019) - Liu, Yang; Zhang, Dongjie; Du, Juan; Qin, Ying; Zhao, Zhigang; Shi, Yanjun; Mei, Shenghui; Liu, Yi
Abstract: Plasma concentrations of nicotine and its active metabolite cotinine are highly correlated with its biological effects. A UHPLC–MS/MS method was developed, validated and applied for nicotine and cotinine analysis in mice plasma. Chromatographic separation was achieved on a BEH HILIC column using acetonitrile (0.1% formic acid) and 10 mm ammonium formate as mobile phase. The gradient elution was performed at 0.4 mL/min with a run time of 3.6 min. The quantitative ion transition was m/z 163.1 > 130.0 for nicotine, m/z 177.1 > 80.0 for cotinine and m/z 167.1 > 134.0 for nicotine‐D4 (internal standard, IS). For both nicotine and cotinine, the calibration range was 5–500 ng/mL with 5 ng/mL as the lower limit of quantitation, and the intra‐ and inter‐day bias and imprecision were −4.61–12.00% and <11.12%. The IS normalized recovery was 90.62–98.95% for nicotine and 89.18–101.53% for cotinine, and the IS normalized matrix factor was 106.00–116.44% for nicotine and 100.34–109.85% for cotinine. Both nicotine and cotinine were stable under conventional storage conditions. The validated method has been applied to a pharmacokinetic study in mice to calculate the pharmacokinetic parameters for both analytes.